Pembaruan Rambu Dangerous Goods Area di Terminal Petikemas Nilam - Wahyu Nur Laili Sutarto; Abdul Hakkim Zakkiy Fasya (Yayasan Literasi Sains Indonesia, 2023)
There are hazards and risks, especially in the work area of ​​Nilam Terminal Port, which can occur because all activities are carried out every day by workers, passengers, or people around the area, such as loading and unloading of goods, boarding and alighting of passengers, equipment maintenance. , lifting and transporting ship services, as well as other supporting activities, of course require space and also qualified tools/materials to support it. However, apart from that, in utilizing the areas or materials needed, there are concerns and risks that will arise because not all areas or materials are safe, in fact there are so many things that are dangerous, so a warning is needed to serve as an appeal to the workforce. and also the passengers in the area to avoid it. Judging from the research conducted at the Patchouli Container Terminal, warning signs such as dangerous goods have not been implemented in the Port Terminal area so that it can increase the risk of work accidents for workers. So the purpose of this research is to analyze and review related to work safety in the Port Terminal area as well as to develop and recommend innovations in the form of hair renewal of dangerous goods area in the Patchouli Container Terminal. The research was used by discussion and observation methods from 5 August to 23 December 2022 at PT Pelindo Terminal Petikemas. Based on the results of the innovation recommended by the author, it is aimed at paying attention to dangerous areas and objects around the terminal in order to minimize and prevent work accidents for workers. In addition, the main goal is to provide health protection and also Occupational Safety and Health (K3) for workers and companies.